Cuban cooperatives before the Sustainable Development Goals:: proposal for a diagnostic instrument - Alemán Salcedo, Eliana; Marín de León, Iriadna (Cooperativismo & Desarrollo, 2022)
Based on a critical review of the Cooperative Social Responsibility Management Model (MGRSC), a diagnostic instrument is proposed to identify the contribution of Cuban cooperatives to the Sustainable Development Goals (SDG) and a methodology for its use. For this, a qualitative documentary study was carried out on social responsibility models. The procedures used were analysis and synthesis. The research shows that the evaluation of the social performance of cooperatives serves to estimate their contribution to the SDGs, although in its conception the MGRSC did not incorporate the measurement and evaluation of the contribution of cooperatives to the SDGs. There is also a gnoseological vision of cooperatives by leaving out other dimensions that allow us to understand why in most Cuban cooperatives their social management practices are isolated and spontaneous. In this regard, a battery of 50 indicators is proposed that contribute to the diagnosis phase and that align social performance, cooperative principles, and SDG. The use of indicators is recommended within an Action Research process that promotes their critical appropriation and drives an organizational change that recognizes the context of the cooperative and the perspective of its members.
Keywords: social economy; indicators; investigation action; cooperative social responsibility; sustainable development goals